Tissue-specific responses to oxidative fuel source preference during heat stress in lactating dairy cows - M.D. Ellett; K.M. Daniels; M.D. Hanigan; B.A. Corl; G. Perez-Hernandez; C.L.M. Parsons; J.A. Melvin; D.W. Fausnacht; R.P. McMillan; L.H. Baumgard; R.P. Rhoads (JDS Communications)
Prolonged exposure to high environmental temperatures results in an accumulated heat load that induces a heat stress (HS) response in dairy cattle. Heat stress compromises dairy farm profitability by reducing milk yield, altering milk composition, and hindering reproductive performance. The ability to alternate between carbohydrate and lipid sources for energy production is termed metabolic flexibility (Met Flex). The objective of this study was to evaluate the Met Flex of mammary, muscle, and liver tissue in lactating dairy cows under HS and thermoneutral (TN) conditions. Sixteen Holstein cows were assigned to 1 of 2 treatment groups: pair-feeding in TN conditions (PFTN) or HS conditions. All cows experienced a 4-d TN period with ad libitum intake followed by a 4-d treatment period. Heat stress cows were exposed to a temperature-humidity index (THI) ranging from 76 to 80 and the PFTN cows were exposed to a THI of 64. Milk production and health data were recorded twice daily. Semitendinosus biopsies were obtained on d 4 of each period and postmortem mammary and liver samples were obtained on d 4 of period 2. All tissue samples were assayed for Met Flex. Activity of mitochondrial (Mit) enzymes were assessed in skeletal muscle only. Four days of HS decreased milk yield, altered milk composition, and increased respiration rate and rectal temperatures. No differences in Met Flex were observed in mammary or liver tissue during period 2. However, HS, but not PFTN conditions, lowered Met Flex of skeletal muscle by 18.3% when compared with TN ad libitum feed intake conditions of period 1. No treatment differences were observed in skeletal muscle Mit enzyme activity indicating the decrease in Met Flex occurred independently of changes in Mit function. The reduction in Met Flex of skeletal muscle during HS may contribute to reduced milk yield and warrants further investigation.